مفهوم الأزمات و طرق إدارتها - حيدر رنا (Latakia University Journal - Economic and Legal Sciences Series, 2018)
شهد العالم في الآونة الأخيرة سلسلة من الأزمات و كذلك الكوارث الطبيعية والاصطناعية والبيئية وغيرها المولدة لأزمات عديدة, مما جعل العلماء يطلقون عليه اسم عصر الأزمات. ونظراً للخسائر المادية والبشرية الهائلة التي قد تنجم عن الأزمات, كان لا بد من التحضير وإعداد العدة لها حتى قبل وقوعها. ونتيجة لذلك نشأ علم إدارة الأزمات وتطور حتى وصل إلى ما هو عليه اليوم. ولكن بالرغم من حداثة عهده إلا أنه يشمل اليوم مبادئ أساسية وعامة لإدارة الأزمات مهما كان حجمها ونوعها. وهنا يجب التنويه إلى أن إدارة الأزمة لا تقتصر على مواجهتها حين وقوعها وإنما يجب معالجة تداعياتها ونتائجها وقبل هذا كله يجب الاستعداد لها قبل وقوعها وحتى منعها من الوقوع – إن أمكن – لتفادي ما يمكن تفاديه من الخسائر المادية والبشرية. وهذا كله يتطلب عدة احتياجات مادية وبشرية وتقنية ومالية وإعلامية وغيرها, مما يعني لزوم تخصيص ميزانية من قبل الدولة وبشكل سنوي للوقاية من الأزمات أو مواجهتها إن لم تفلح الوقاية. بالإضافة إلى ذلك يجب تدريب الأشخاص القائمين على إدارة الأزمة وتأهيلهم بشكل مستمر ليتمكنوا من التعامل معها بطريقة سليمة وفي أي وقت. The world has seen in recent series of crises, as well as natural disasters and man-made, environmental and other generated many crises, making the scientists call it the era of crises name. Because of the enormous material and human losses that may result from the crisis, it was necessary to prepare and mount them even before they occur. As a result, he grew up aware of crisis management and the evolution until he reached what it is today. But despite the recent reign but today it includes the basic principles and the general crisis management regardless of their size and type. Should be noted that crisis management is not confined to confront them when they occur and must be dealt with its implications and consequences, and before this whole must prepare for them before they occur and even prevent it from falling - if possible - to avoid what can be avoided, material and human losses. All this requires several needs of material and human, technical and financial, media and other. Which means unnecessary budget allocation by the state on a yearly basis for the prevention of crisis or face the failed prevention. In addition to this must be trained persons engaged in the crisis management and rehabilitation of continuously to be able to respond properly and at any time.